2022
DOI: 10.1128/spectrum.00830-22
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus NS4A Protein Interacts with PTEN-Induced Kinase 1 (PINK1) and Promotes Mitophagy in Infected Cells

Abstract: The JEV-infected mammalian cells show an enhanced mitophagy flux with a concomitant decline in the mitochondrial mass. We show that the NS4A protein of JEV localized to the mitochondria and interacted with PINK1 in Huh7 cells during infection with the virus and demonstrate that JEV-NS4A alone is sufficient to induce mitophagy. The study provides the first evidence of mitochondrial quality control dysregulation during JEV infection, largely mediated by its NS4A protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Our data indicated that Drp-1-deficient MDBK cells upon NCP BVDV infection showed an elongated or enlarged mitochondrial morphology compared to NCP BVDV-infected cells alone (Figure 2 C). Previous studies have shown that mitochondrial fission induced by viral infection is important for virus propagation [ 32 , 33 ]. Thus, we speculate that the induction of mitochondrial fission is important for BVDV replication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data indicated that Drp-1-deficient MDBK cells upon NCP BVDV infection showed an elongated or enlarged mitochondrial morphology compared to NCP BVDV-infected cells alone (Figure 2 C). Previous studies have shown that mitochondrial fission induced by viral infection is important for virus propagation [ 32 , 33 ]. Thus, we speculate that the induction of mitochondrial fission is important for BVDV replication.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial dynamics and mitophagy are two critical arms, which are required to maintain mitochondrial homeostasis [ 47 ]. Previous studies have shown that some viruses can induce mitophagy to evade the innate immune response for their persistent infection [ 33 , 48 , 49 ]. Here, we demonstrate that NCP BVDV stimulates upregulation of Drp1 and Drp1 (Ser616) expression, and promotes the recruitment of Drp1 to damaged mitochondria, which lead to mitochondrial fission and subsequent clearance of damaged mitochondria by Parkin-dependent complete mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that JEV utilizes the lysosomes membrane for RNA replication and hijacks the autophagic machinery to benefit virus replication ( 50 ). It has been reported that JEV NS4A induces mitophagy to promote viral infection, and inhibiting either mitochondrial fragmentation or mitophagy impairs virus propagation ( 51 ). The autophagy inhibitors reduce JEV infection and weaken the inflammatory response in mice ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…DENV infection induces mitochondrial elongation or fragmentation to promote viral replication ( Yu et al, 2015 ; Chatel-Chaix et al, 2016 ; Barbier et al, 2017 ). HCV and JEV viral proteins are enriched in mitochondria and promote mitochondrial fragmentation and mitophagy ( Ruggieri et al, 2014 ; Siu et al, 2016 ; Kim et al, 2017 ; Qu et al, 2019 ; Agarwal et al, 2022 ). In the present study, we found that NSP1 reduced the expression of mitochondrial marker proteins TOM20 and TIM23; decreased the autophagy-related protein p62, and increased the autophagy marker protein LC3B, indicating that NSP1 may induce mitophagy.…”
Section: Discussionmentioning
confidence: 99%